The Differential Effect of Community-Based Supplementary Feeding on Wasting and Stunting: Epidemiological Evidence from an Endemic Region in West Nusa Tenggara - Yamin, Imam Syahputra; Rahmawati, Santi Deliani; Furqan, Baiq Repika Nurul (PT. LARPA JAYA PUBLISHER, 2026)
Stunting remains a persistent public health challenge in Indonesia, particularly within high-prevalence enclaves. Although local food-based Supplementary Feeding Programs (SFP) are widely implemented, their specific epidemiological impact on anthropometric indices specifically the divergence between weight and height recovery requires rigorous evaluation in high-burden settings. This study aimed to analyze the effectiveness of a 90-day local food-based SFP intervention on anthropometric Z-score shifts among stunted toddlers in Setungkep Lingsar Village, East Lombok. A quasi-experimental study with a one-group pretest-posttest design was conducted on a total population of 59 stunted toddlers (aged 6–59 months). Anthropometric measurements (Weight, Height) and WHO standard indices (Weight-for-Age [WAZ], Height-for-Age [HAZ], and Weight-for-Height [WHZ]) were assessed pre- and post-intervention. Data were analyzed using the Paired Sample t-test with statistical significance set at p<0.05. The intervention yielded statistically significant improvements across all growth parameters (p=0.0001). The most rapid response was observed in acute nutritional indicators; the prevalence of normal nutritional status based on Weight-for-Height (WHZ) increased substantially from 10.2% to 46.9%, with a mean weight gain of 0.45 kg. Conversely, although Height-for-Age (HAZ) showed statistical improvement, the clinical shift from stunted to normal status remained minimal (2.0%), confirming a physiological lag in linear growth recovery compared to ponderal (weight) recovery. Local food-based SFP is highly effective for the rapid correction of acute malnutrition (wasting) but requires a sustained maintenance phase to achieve significant catch-up growth for stunting. Policy strategies in high-burden regions must extend monitoring beyond the acute recovery phase to ensure long-term linear growth rehabilitation.